2019
DOI: 10.1093/europace/euz342
|View full text |Cite
|
Sign up to set email alerts
|

Safety and outcome of very high-power short-duration ablation using 70 W for pulmonary vein isolation in patients with paroxysmal atrial fibrillation

Abstract: Aims Pulmonary vein isolation (PVI) using radiofrequency ablation (RFA) in patients with paroxysmal atrial fibrillation (PAF) is effective but hampered by pulmonary vein reconnection due to insufficient ablation lesions. High-power delivery over a short period of time (HPSD) in RFA is stated to create more efficient lesions. The aim of this study was to compare intraprocedural safety and outcome of HPSD ablation to conventional power settings in patients undergoing PVI for PAF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
221
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(231 citation statements)
references
References 16 publications
7
221
2
1
Order By: Relevance
“…This study also had the highest effect size among the three studies that demonstrated a significant association between HPSD and the increased freedom from AT. 17,18,27 The study by Kottmaier et al 17 was the only included study that used a significantly higher power of 70 W for 5-7 s and was also demonstrated significantly higher atrial arrhythmia recurrences with LPLD (32.3% vs. 14.2%, OR = 2.73, 95%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also had the highest effect size among the three studies that demonstrated a significant association between HPSD and the increased freedom from AT. 17,18,27 The study by Kottmaier et al 17 was the only included study that used a significantly higher power of 70 W for 5-7 s and was also demonstrated significantly higher atrial arrhythmia recurrences with LPLD (32.3% vs. 14.2%, OR = 2.73, 95%…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies from 2006 to 2020 involving 2274 patients were included (1393 patients underwent HPSD strategy and 881 patients underwent LPLD strategy). 10,[15][16][17][18][19][20][21][22]27 There were six in the…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…A significant difference in power delivery setting was found between the HPSD and LPLD groups. There is no consensus about the power and duration settings for HPSD, in our study, energy levels above 40 W are considered as high power and duration of application for 2˜10s as short duration 4,13,14,[17][18][19][20] . All patients received PVI, additional linear ablations were performed in select patients at the operator's discretion in some trials 4,18,19 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous clinical studies have evaluated the HPSD ablation during the PVI procedure using several endpoints for each RF application, such as the RF time, 10‐14 CF‐related indices (ablation index 11,15‐17 and lesion size index 11,18 ), and loss of pacing capture during the RF delivery 18 . However, little is known about high‐power RF ablation for a PVI using USM as a guide for the local endpoint of each RF application 19 …”
Section: Discussionmentioning
confidence: 99%